Application of two-dimensional detection based on the background subtraction in badminton Hawkeye system - Li, L. (Advances in Intelligent Systems Research, 2015)
With the development of computer technology, computer vision technology was getting more mature. The two-dimensional detection in the badminton Hawkeye system was studied with background subtraction. The mass center coordinates of the badminton were obtained after eliminating the influence of the isolated noise by morphological opening operation, which have found the base of badminton 3D information obtaining and reconstruction for the following research